2013
DOI: 10.4236/anp.2013.23037
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of Nanofluids. Why It Is Not Described by the Classical Theories

Abstract: Transport properties of nanofluids are extensively studied last decade. This has been motivated by the use of nanosized systems in various applications. The viscosity of nanofluids is of great significance as the application of nanofluids is always associated with their flow. However, despite the fairly large amount of available experimental information, there is a lack of systematic data on this issue and experimental results are often contradictory. The purpose of this review is to identify the typical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(53 citation statements)
references
References 46 publications
2
48
0
3
Order By: Relevance
“…A previous study found that the issue with researches into viscosity of nanofluids is that they lack systematic data and the experimental data are always antithetical [36]. A possible explanation as to why the nanofluids samples had a lower viscosity than standard deionised water, as occurred in Figure 3 (a), is that apparatus used for viscosity test was a Brookfield DV-II+ Pro Viscometer with an SC4-18 spindle.…”
Section: Viscositymentioning
confidence: 99%
“…A previous study found that the issue with researches into viscosity of nanofluids is that they lack systematic data and the experimental data are always antithetical [36]. A possible explanation as to why the nanofluids samples had a lower viscosity than standard deionised water, as occurred in Figure 3 (a), is that apparatus used for viscosity test was a Brookfield DV-II+ Pro Viscometer with an SC4-18 spindle.…”
Section: Viscositymentioning
confidence: 99%
“…Сегодня уже ясно, что они не стандартны и не описы-ваются классическими теориями для крупнодисперсных жидкостей. С вязкостью такое понимание практически достигнуто (см., например, работы [4][5][6][7][8][9] и цитирован-ную там литературу). Показано (и экспериментально, и молекулярно-динамическим моделированием), что вяз-кость наножидкостей существенно превосходит вязкость крупнодисперсных жидкостей при той же объемной концентрации наночастиц.…”
Section: Introductionunclassified
“…At relatively small concentration of the nanoparticles, it is widely admitted (e.g. [1][2][3][4][5][6][7][8]), that η is either a linear or a quadratic function of the volume fraction φ of dispersed particles. As our main objective is to focus on the study of size effect, we shall, as a first approximation, take for η the simplest φ-dependence, namely the linear law η= ηf (1+αφ),…”
Section: Effective Viscosity Of Nanofluidsmentioning
confidence: 99%
“…The nanoparticles are assumed to be rigid spheres uniformly dispersed in the fluid carrier, the temperature is fixed at T= 300 K and volume fraction of particles is small, ranging from 0.01 to 0.10. As our aim is not to find the best dependence of the viscosity with particle concentration, we have selected for it the simplest linear law with the coefficient α= 2.5 as suggested by Einstein [11] rather than more complicated laws with ad hoc values [1,38] The radius r of the nanoparticles Li is ranging from 1 to 4 nm. As for the mean free path l, we start from Matthiessen's rule stating that 1/ = 1/ + 1/ + 1/ , with , , designating the mean free path associated to collisions between Ar-Ar, Li-Li and Ar-Li molecules respectively.…”
Section: Nanoparticles Dispersed In Liquid Armentioning
confidence: 99%
See 1 more Smart Citation